Contemporary Zakat Governance in Realizing Community Welfare in Siak Regency: A Maqāṣidī Interpretation Approach - Abdul Munzir; Lukmanul Hakim (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Zakat management in the contemporary era faces challenges not only in the collection aspect, but also in the effectiveness of governance and its relevance in realizing sustainable community welfare. The main problem of this research is the extent to which zakat governance carried out by BAZNAS Siak Regency has been aligned with the objectives of the Qur'an (maqāṣid al-Qur'ān) and contributed significantly to improving the welfare of mustahik. This study aims to analyze the practice of zakat management in Siak Regency through the maqāṣidī interpretation approach, emphasizing the orientation of zakat as an instrument of social and economic empowerment. The method used is qualitative-normative research with a descriptive-analytical approach, through the study of Qur'anic verses on zakat, contemporary maqāṣidī interpretation literature, and empirical data on zakat management and distribution of BAZNAS Siak Regency. The results of the study indicate that zakat governance in Siak Regency, through programs such as Smart Siak, Healthy Siak, and Prosperous Siak, has generally been in line with the maqāṣid al-Qur'ān, especially in the aspects of welfare equality, protection of human dignity, and economic empowerment of mustahik. The increase in zakat collection to Rp4.8 billion in Ramadhan 1446 H reflects institutional effectiveness and increased public trust. However, this study also found challenges in the form of limited integration of mustahik data and the need to expand productive zakat. This study concludes that zakat in Siak Regency has functioned as a welfare instrument oriented towards Qur'anic goals, but still requires strengthening of governance for a more sustainable impact.